Supervening Impossibility and the Supplier’s Duty to Perform in terms of Section 19 of the Consumer Protection Act, 2008 – National Consumer Commission v Crystal Tears Investment 206 CC t/a Misty River and Elizabeth Hoogenhout t/a Misty River CT/261684/20 - Mark Tait (Obiter, 2024)
One of the many negative consequences of the COVID-19 pandemic, during which South Africa was subjected to restrictions imposed owing to the pandemic, was the many terminations of numerous bookings and reservations for the provision of services such as travel, accommodation, and the hosting of weddings. In National Consumer Commission v Crystal Tears Investment 206 CC t/a Misty River and Elizabeth Hoogenhout t/a Misty River (NCT/261684/2023/73(2)(b)), the consumer had booked a venue for her forthcoming wedding and had paid a substantial amount towards the costs of the wedding celebration. The occasion had to be cancelled owing to the imposition of lockdown restrictions imposed by the government and, unfortunately, the parties could not reach an agreement about postponing the event. The consumer demanded repayment of monies already paid, which the supplier refused. The matter was referred to the Tribunal, which held that certain provisions of section 19 of the Consumer Protection Act, (68 of 2008) (CPA) applied and that the supplier was therefore liable to refund the consumer. The Tribunal also imposed an administrative fine on the supplier.Although it is agreed that the supplier was indeed liable to refund the monies paid by the consumer, it is respectfully argued that the Tribunal was incorrect in finding that the supplier was in breach of the provisions of section 19 of the CPA. It is argued that the provisions in question cannot be relied upon in the event that the contract between the consumer and the supplier was terminated owing to an event of supervening impossibility, as it is argued the imposition of the lockdown restrictions constituted.The matter also allows some reflection on aspects of section 19.